2021
DOI: 10.3390/children8020059
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Suicide in Our Community through the Lens of the Pediatric ICU: An Epidemiological Review (2011–2017) of One Midwestern City in the US

Abstract: Suicide frequency has tripled for some pediatric age groups over the last decade, of which, serious attempts result in pediatric intensive care unit (PICU) admissions. We paired clinical, aggregate geospatial, and temporal demographics to understand local community variables to determine if epidemiological patterns emerge that associate with risk for PICU admission. Data were extracted at an urban, high-volume, quaternary care facility from January 2011 to December 2017 via ICD 10 codes associated with suicide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This is important, since nonfatal self-harm is an independent and significant risk factor for repeated attempts and increased risk of completed suicides (8)(9)(10)(11)(12). In a single-center study of 1,036 patients hospitalized for self-harm, of which 161 were admitted to the PICU (13), patients admitted to the PICU were also predominantly female (64%), were White (83%), and had ingestion as the most common mode of self-harm (66%). As in our study, their observed hospital mortality was low (1.9%), but a greater proportion of patients in that study were discharged home from the PICU (19.3%) compared with ours (7.9%) (13).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, since nonfatal self-harm is an independent and significant risk factor for repeated attempts and increased risk of completed suicides (8)(9)(10)(11)(12). In a single-center study of 1,036 patients hospitalized for self-harm, of which 161 were admitted to the PICU (13), patients admitted to the PICU were also predominantly female (64%), were White (83%), and had ingestion as the most common mode of self-harm (66%). As in our study, their observed hospital mortality was low (1.9%), but a greater proportion of patients in that study were discharged home from the PICU (19.3%) compared with ours (7.9%) (13).…”
Section: Discussionmentioning
confidence: 99%